Risk Assessment of Dropped Objects on Topside Facilities and Subsea Pipelines - F. Irfan Ahmad Fuad, M; A Zakwan Hamidi, M; Ammar Abidin, M; Abdul Rashid, Z; Abdul Razak, K (International Journal of Engineering and Technology, 2018)
Falling object and swinging load impacts due to mechanical handling failures can occur in industrial facilities both onshore and offshore. The risk of accidental dropped object is considered as one of major risk categories predominantly in offshore production platform. As part of the offshore platform engineering design development, there is a need to consider the potential risk arising from falling object and swinging load impacts during routine and non-routine lifting activities utilizing platform pedestal crane. Dropped Object Risk Study as part of formal safety assessment is predominantly used to support the design of an offshore platform. The interest is focused on impacts to platform designated laydown area, structures, process equipment and subsea pipelines. The consequences from such events may include injuries or fatalities among personnel underneath, damage to equipment containing hydrocarbons onboard and subsea pipelines (overboard) resulting to leaks and hydrocarbon fires in extreme cases and damage to the platform structure either localized or as a whole. The results and findings from dropped object risk study will be used to specify requirements for engineered and operational safeguards to mitigate the risks. These include requirement of adequate integrity of deck/laydown or restriction on lifting pathways.Â Â